Talented and Gifted Mentors for the Promotion of Motivation, Educational, and Research Activities of Nursing Students - Elaheh Mianehsaz; Fakhrosadat Mirhosseini; Fatemeh Hajirezaei Kashan; Leila Saharkhan; Mohammad Javad Azadchehr; Mohsen Taghadosi; Fatemeh Ebrahimzadeh; Hakime Zamani-Badi (Strides in Development of Medical Education, 2022)
Background: Having a mentor affects nursing students' academic achievement and motivation.Objectives: This study aimed to investigate the effects of the mentoring program delivered by talented and gifted postgraduate students on motivation, academic achievement, and research activities of undergraduate nursing students of Kashan University of Medical Sciences in 2020.Methods: In this formal mentoring program designed as quasi-experimental pre-post-test design research, 29 out of 37 eligible undergraduate nursing students with a low-grade point average (GPA) enrolled voluntarily. After completing the Science Motivation Questionnaire (SMQ), 21 students with low or moderate motivation entered the study as part of either mentee (n=10) or the control group (n=11). Five talented master's degree students were selected as mentors, each joining with two mentees and leading them through specific programs during one semester. At the beginning and end of the semester, students' academic motivation, the number of research activities, and educational performance were evaluated and analyzed by covariance (ANCOVA) and paired t-tests.Results: The students in the mentee group had higher academic motivation than the control group (P = 0.05); 80% of mentees had more than one research activity, while the controls had no research activities (P<0.001), and there was no significant difference between the two groups in the Grade Point Average (GPA) (P=0.110).Conclusion: Talented students could play the role of mentors well, and applying a mentoring program enhanced undergraduate nursing students' academic motivation and research activities and prevented a decline in their GPAs.